KEBIJAKAN PENCEGAHAN PELECEHAN SEKSUAL TERHADAP ANAK: MASUKAN BAGI PRAKTISI SOSIAL - Mu'man Nuryana (Politeknik Kesejahteraan Sosial, 2004)
Children Sexual Abuse Prevention Policy: An Input for Practitioners.Many literatures show that there are no differences of background in term of socioeconomic of victims and perpetrators of sexual abuse in family and community. It's also give information that victim of sexual abuse is categorized as a